Features of the Interaction between Teachers and Students in Conditions of Mixed Learning - PONOMAROV, Oleksandr (Journal of Research in Educational Sciences; Vol 14 No 16 (2023): JRES, Volume XIV, Issue 16, Winter 2023DO - 10.14505/jres.v14.16.05, 2023)
The article is devoted to communicative technologies of blended learning as one of the most important areas of development of the educational process in higher education institutions. The author analyzes the main aspects and features of interaction between teachers and students in conditions of blended learning, the main advantages and disadvantages of such interaction. The practical implementation of information and communication models based on the functioning of modular object-oriented learning environments is studied. Based on the analysis, the author has developed the rules of communication between the teacher and students, which will make the educational process in conditions of blended learning more effective.